PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI SEKTOR INDUSTRI BARANG KONSUMSI: PERAN PERTUMBUHAN PERUSAHAAN, LEVERAGE, DAN LIKUIDITAS - Falah Arnori Adha; Hotman Fredy; Herlan (RELEVAN : Jurnal Riset Akuntansi, 2023)
The purpose of this study is to ascertain how company growth, leverage, and liquidity will affect profitability in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for 2018 to 2021. The variables in this study use the analysis of company growth, leverage, liquidity, and probability ratio (ROA). The data used is secondary data information from publicly available annual financial reports. The sample of this study consisted of 17 companies out of a total of 68 samples using purposive sampling technique. For data processing using views 12 software using panel data regression analysis, classical assumption test, and hypothesis testing as data testing methods. The results showed that company growth has no effect on probability, while leverage has an influence on it, as well as liquidity has an influence on profitability.